Denotation and Connotation of Mandau, A Weapon of Kanayatn Dayak Tribe in West Kalimantan - Iwan Pranoto; Nur Iksan; Ika Yuliati (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2023)
The culture and the cultural product itself that develop in today’s society cannot be separated from the recognition and agreement of some community groups, the philosophical values, or the natural signs that are embedded in everyday life, or usually called myths. One of them is Mandau, a weapon of the Kanayatn Dayak tribe, in Sebetuk village, Ngabang sub-district, Landak district, West Kalimantan. The Mandau is a weapon owned by the Kanayatn Dayak people and is often used for many purposes such as cutting the grass, chopping the wood, cutting the meat from hunted animals, protecting themselves from wild animals, conducting traditional rituals and as weapons of war. This Mandau is differentiated into two categories, the one that has sacred value and another one that does not. In this study, the object of research was the one with a scared value. The Mandau that developed in the Kanayatn Dayak community has its own a message and meaning. The denotation and connotation of the Mandau were discussed in this study based on semiotic of Roland Barthes's thought. By employing a qualitative approach, the fine art elements of the Mandau such as the decorative motifs, colors, and shapes became the main discussion. Each of them has its own meaning and thus it is trusted by the local community.